Efficacy and safety of Chinese medicine injection combined with concurrent chemoradiotherapy in the treatment of esophageal cancer: a Bayesian network meta-analysis - Wang, Jiacheng; Xi, Hongbin; Chen, Xuewei; Xin, Yingqian; Wei, Fengqin (Frontiers in Medicine, 2025)
BackgroundEsophageal cancer (EC) is a significant global health concern. Chinese medicine injections (CMIs) are widely utilized as adjunctive therapies for EC. This network meta-analysis (NMA) aimed to compare the efficacy and safety of various CMIs in combination with concurrent chemoradiotherapy (CCRT) for the treatment of EC.MethodsRelevant randomized controlled trials (RCTs) were comprehensively searched in eight electronic databases until August 2024. The quality of eligible RCTs was assessed via the Cochrane Risk of Bias tool (RoB 2.0). Bayesian NMA was conducted through R 4.2.1 and Stata 15.1, with treatment regimens ranked based on the surface under the cumulative ranking curve (SUCRA). The quality of evidence was evaluated using CINeMA.Results54 studies encompassing 4,201 patients and 13 types of CMIs were included. Astragalus polysaccharide injection (HQDT) combined with CCRT (SUCRA: 86.7%) ranked highest for improving clinical effectiveness rate. Kanglaite injection (KLT) combined with CCRT (SUCRA: 85.1%; 90.1%) was optimal for enhancing performance status and one-year survival rate. Kangai injection (KA) combined with CCRT (SUCRA: 97.2%) achieved the greatest improvement in CD3+ levels. Aidi injection (AD) combined with CCRT (SUCRA: 99.9, 99.9%) was most effective in increasing CD4+ and CD8+ levels, while Fufangkushen injection (FFKS) combined with CCRT (SUCRA: 99.9%) yielded the greatest improvement in the CD4+/CD8+ ratio. Based on descriptive statistics, all regimens demonstrated favorable safety profiles, with no serious adverse events (AEs) reported.ConclusionCMIs combined with CCRT appear to provide superior therapeutic efficacy over CCRT alone in the treatment of EC. In particular, HQDT, KLT, KA, AD, and FFKS exhibited the most pronounced benefits across key clinical outcomes. Nevertheless, the findings shall be validated in multicenter, better-designed RCTs.Systematic review registrationThe PRISMA registration details for this study can be found at: https://www.crd.york.ac.uk/PROSPERO/view/CRD42024574242.